2011
DOI: 10.4238/2011.october.31.4
|View full text |Cite
|
Sign up to set email alerts
|

Random regression models using different functions to model test-day milk yield of Brazilian Holstein cows

Abstract: ABSTRACT. We analyzed 152,145 test-day records from 7317 first lactations of Holstein cows recorded from 1995 to 2003. Our objective was to model variations in test-day milk yield during the first lactation of Holstein cows by random regression model (RRM), using various functions in order to obtain adequate and parsimonious models for the estimation of genetic parameters. Test-day milk yields were grouped into weekly classes of days in milk, ranging from 1 to 44 weeks. The contemporary groups were defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
38
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 23 publications
12
38
2
Order By: Relevance
“…The LEG.55_ HE4 resulting in the best index value (Table 1). A similar result was observed by BIGNARDI et al (2011) andSANTOS et al (2014) for Holstein and Guzerá breeds, respectively. BROTHERSTONE et al (2000) observed that the non-linear parametric functions were more appropriate for adjusting the lactation curve of primiparous Holstein cows, compared to orthogonal Legendre polynomials with the same number of parameters.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…The LEG.55_ HE4 resulting in the best index value (Table 1). A similar result was observed by BIGNARDI et al (2011) andSANTOS et al (2014) for Holstein and Guzerá breeds, respectively. BROTHERSTONE et al (2000) observed that the non-linear parametric functions were more appropriate for adjusting the lactation curve of primiparous Holstein cows, compared to orthogonal Legendre polynomials with the same number of parameters.…”
Section: Resultssupporting
confidence: 73%
“…The additive genetic variance estimated by the four models decreased from the first (@ 31.50) until the 17 th fortnight (@12.15), and increased at the end of lactation, where the WF.33_HE2 and LEG.33_HE2 reached values close to 19.00 and the LEG.55_HE4 reached 14.85 ( Figure 1A). Similar behavior was observed by BIGNARDI et al (2011) andPEREIRA et al (2010) for Holstein and Gir breed cows, respectively.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…TDMs analyzes individual test-day records instead of 305 day milk yields of cows, which are currently used by Ptak and Schaeffer [6] , Swalve [7] , Jamrozik and Schaeffer [8] , Pool and Meuwissen [9] , Schaeffer et al [10] , Takma and Akbas [11] , Takma and Akbas [12] , Bignardi et al [13] , Galic and Kumlu [14] .…”
Section: A Comparison Of Some Random Regression Models For First Lactmentioning
confidence: 99%